Student Satisfaction Level Analysis Of Online Learning During Pandemic Covid 19 Using C5.0 Algorithm - James Hasudungan Sihombing (Yayasan Kita Menulis, 2022)
The Simalungun University Foundation Tourism Vocational School is a private school located in Pematangsiantar. At this time there are problems in the learning process. And currently the data collection used by researchers in obtaining student satisfaction data is by sampling. In this study, data were obtained from giving questionnaires to students of the Simalungun University Foundation Tourism Vocational School which were categorized using five variables, namely teaching methods, learning media, communication, teaching materials/modules, and learning duration. Data Mining using the C5.0 algorithm is proven in analyzing satisfaction in the teaching and learning process. Research result able to find out the results of the analysis of the level of student satisfaction with online learning and find the highest score, can help the Tourism Vocational School of the Simalungun University Pematangsiantar Foundation in optimizing online learning today.